Impact of Advanced Trauma Life Support Training for Improving Mortality Outcome: A Systematic Review and Meta-analysis - Putra, Afid B; Nurachman, Luthfian A; Suryawiditya, Bagus A; Risyaldi, Muftah; Sihardo, Lam (The New Ropanasuri Journal of Surgery, 2023)
Introduction. The Global Burden of Disease Study has identified injuries as one of the top ten causes of death and disability worldwide. Injury is predicted to rise in the rankings by the year 2030. This study aimed to quantify the effectiveness of an Advanced Trauma Life Support (ATLS) training in improving mortality outcome after trauma injury. Method. This is a systematic review (of experimental and observational studies) and meta-analysis, reporting mortality outcome from trauma injury between ATLS-trained/certified physicians vs non-ATLS-certified. We performed literature searching through 3 electronic databases, including Cochrane (CENTRAL), MEDLINE (PubMed), and Scopus. Results. There are summarized results from 7 selected articles. The total patients included in this analysis were 11,595 patients in post-ATLS group and 21,603 patients in pre-ATLS group. There was high heterogeneity among studies (I2 = 95%) and therefore random effect model was used for analysis. Pooled analysis showed that ATLS had no significant effect in reducing the risk of mortality (OR: 0.68; 95% CI 0.39 – 1.20; p = 0.18). Although ATLS is not significantly associated with improved mortality outcomes, this meta-analysis has shown a tendency that health facilities and health workers implementing ATLS experienced lower mortality. Conclusion. ATLS is not the only aspect that contributes to patients’ survival. There are also roles in pre-emergency settings, resource availability, and experience. However, we believe that implementing the ATLS protocol in healthcare facilities will be the leading factor in improving trauma patients' management.